Art and Politics of Things: Bruno Latour’s Curatorship and the Reconfiguration of Mediations in the Contemporary Era - Murari, Victor Tuon (Farol, 2025)
This study investigates Bruno Latour’s curatorial strategies in the exhibitions "Iconoclash," "Making Things Public," and "Reset Modernity!", analyzing how the French sociologist uses art to challenge traditional conceptions of modernity, science, and politics. Through an interdisciplinary approach, the research demonstrates that the exhibitions function as conceptual laboratories that problematize the separation between nature and culture, proposing a more complex and relational vision of social reality. The results reveal that Latour develops key concepts such as "iconoclash" and "politics of things" to reconfigure our understanding of agency and representation. We conclude that Latour’s curatorial interventions constitute a radical critique of modern thought, offering an innovative perspective for understanding contemporary challenges, especially in the context of the Anthropocene.